Chemokine Receptor 5, a Double-Edged Sword in Metabolic Syndrome and Cardiovascular Disease - Zhang, Zhongwen; Wang, Qiannan; Yao, Jinming; Zhou, Xiaojun; Zhao, Junyu; Zhang, Xiaoqian; Dong, Jianjun; Liao, Lin (Frontiers in Pharmacology, 2020)
The key characteristic of cardiovascular disease (CVD) is endothelial dysfunction, which is likely the consequence of inflammation. It is well demonstrated that chemokines and its receptors play a crucial role in regulating inflammatory response, and recently much attention has been paid to chemokine receptor 5 (CCR5) and its ligands. For example, CCR5 aggravates the inflammatory response in adipose tissue by regulating macrophage recruitment and M1/M2 phenotype switch, thus causing insulin resistance and obesity. Inhibition of CCR5 expression reduces the aggregation of pro-atherogenic cytokines to the site of arterial injury. However, targeting CCR5 is not always valid, and emerging evidence has shown that CCR5 facilitates progenitor cell recruitment and promotes vascular endothelial cell repair. In this paper, we provide recent insights into the role of CCR5 and its ligands in metabolic syndrome as related to cardiovascular disease, the opportunities and roadblocks in targeting CCR5 and its ligands.